Your greater is coming : discover the path to your bigger, better, and brighter future - Osteen, Joel (FaithWords, 2022)
"New York Times bestselling author and host of the Joel Osteen Radio on SiriusXM wants you to know that now is the time to get your hopes up and start expecting that better is on the way. Whether you're climbing toward the next level, stretching for an out-of-reach goal, or doing your utmost to overcome a challenge, it's time to step into a better life filled with more. When your patience strains to meet your expectations, you have to remember that where you are now is not where you're about to be! In Your Greater Is Coming, #1 New York Times bestselling author Joel Osteen challenges your perception of your present situation and inspires you to persevere for the best that's just ahead. Whatever you're experiencing, don't lose faith or give up on your dreams. Wait for your greater, because your greater is coming-greater joy, greater strength, greater relationships. Greater opportunities, greater success, and greater peace are all yours. Whatever you've been waiting for, working for, praying for, and hoping for is on the way. Your Greater Is Coming will nourish your soul and empower your heart to push through pain and master the mundane. Your story is far from over, and the best is yet to come. Don't give up just as you're about to discover a new level of increase, ease, and joy. Glimpse your breakthrough just ahead and hold on just a little longer-your greater is coming!"--